Cost-effectiveness of a mobile-phone text messaging intervention on type 2 diabetes—A randomized-controlled trial. Issue 1 (March 2020) - Islam, Sheikh Mohammed Shariful; Peiffer, Ralph; Chow, Clara K; Maddison, Ralph; Lechner, Andreas; Holle, Rolf; Niessen, Louis; Laxy, Michael
Highlights: The mobile phone text-messaging is an effective and cost-effective method in improving glycemic control. Text-messaging might be a valuable addition to standard treatment for diabetes care in low-resource settings. Abstract: Aims: To evaluate the cost-effectiveness of a mobile phone text messaging program for people with type 2 diabetes mellitus. Methods: We performed a generalized cost-effectiveness analysis in a randomized controlled trial in Bangladesh. Patients with type 2 diabetes were randomized (1:1) to a text messaging intervention plus standard-care or standard-care alone. Intervention participants received a text message daily for 6 months encouraging healthy lifestyles. Costs to users and the health systems were measured. The EQ-5D-3L was used to measure improvements in health-related quality-adjusted life years (QALYs). Intervention costs were expressed as average cost-effectiveness ratios (cost-per 1% unit-reduction in glycated haemoglobin HbA1c and cost per QALY gained), based on the World Health Organization cost effectiveness and strategic planning (WHO-CHOICE) method. Results: In 236 patients [mean age 48 (SD9.6) years] the adjusted difference in accumulated QALYs between the intervention and the control group over the 6-month period was 0.010 (95%CI: 0.000; 0.021). Additional costs per-patient averaged 24 international dollars (Intl.$), resulting in incremental cost-effectiveness ratios of 38 Intl.$ per % glycated haemoglobin (HbA1c) reduction and 2406 Intl.$ per QALY gained. The total intervention costs for the mobile phone text messaging program was 2842 Int.$. Conclusion: Text messaging might be a valuable addition to standard treatment for diabetes care in low-resource settings and predicted to lead an overall saving in health systems costs. Studies with longer follow-up and larger samples are needed to draw reliable conclusions.